Acute alcohol intoxication among adolescents in Italy, the Netherlands and Belgium: a cross-national hospital chart comparison study - Stijn Verhulst; Nico van der Lely; Andrea Orsi; Giancarlo Icardi; Guido Van Hal; Hanna van Roozendaal; Louise Pigeaud; Allegra Ferrari; Loes de Veld; Inge Glazemakers; Jozef De Dooy (BMJ Paediatrics Open)
Background Excessive drinking among adolescents in Western Europe is prevalent, posing significant health risks and societal costs. Comprehensive data on adolescent drinking patterns is crucial for developing effective prevention strategies. Data on alcohol intoxication among adolescents provide valuable insights in this context.Methods To gain insight into the demographic and clinical characteristics of acute alcohol intoxication (AAI) across European countries, we analysed emergency department data on AAI among adolescents (aged 14–17) from 2015 to 2023 in three urban regions: Genoa (Italy), Delft (the Netherlands) and Antwerp (Belgium).Results Out of 1826 admissions, Belgium had the highest median annual admission rate (51 per 10 000 adolescents), followed by the Netherlands (49 per 10 000) and Italy (37 per 10 000). The median age of patients was 16 years across all countries. Sex was equally distributed among Dutch patients; however, in Italy (not statistically significant, 55.6%) and Belgium (statistically significant, 56.8%), more males were admitted. The median blood alcohol concentration (BAC) was higher in the Netherlands (2.00 g/L) compared with Italy and Belgium (1.84 g/L and 1.97 g/L, respectively). This difference remained statistically significant after adjusting for confounders in a multiple linear regression model on BAC. Finally, the proportion of patients with combined drug use (10.4% of the total population) was similar across the three countries.Conclusions This is the first international study to consolidate data on AAI in minors from multiple countries, emphasising the need for a unified European database on AAI in adolescents to enhance prevention efforts.